Financing Low-Cost Housing in Malaysia - Ebekoziena, Andrew; Abdul-Aziz, Abdul-Rashid; Jaafar, Mastura (School of Social Sciences, USM, 2017)
The purpose of this paper is to identify and analyse the methods of housing finance adopted by the low-income earners (both formal and informal) with a view to mitigating the hindrances faced by low-income earners (LIE) when accessing house loan in Malaysia. This was necessitated because low-income house-buyers faced severe problems in gaining access to credit at affordable rates from private banking institutions. Hence, this paper presents the part-findings of an ongoing study that reveals the various methods of financing low-cost housing (LCH) as adopted by LIE in Malaysia. To achieve this, data were collected via in-depth interviews and validated via secondary sources. Thematic analysis was adopted for the qualitative research and 3 themes (sources of LCH finance, encumbrances faced by LIE, and ways to mitigate) were generated. Four states and one territory in Malaysia were covered. The study categorised the sources of LCH financing into two (private and public sector credit institutions). From the findings, ineligibility, down payment, hidden charges and reluctance by banks to lend to LIE were identified by the participants as the major challenges of LCH finance facing the LIE in Malaysia. The supervisory role expected from Bank Negara Malaysia should be resuscitated with a view to ensuring that mortgage institutions total compliance to the mandate given to them in respect of house loan to LIE is accomplished. Also, 2011 Malaysian National Housing Policy should be fully implemented and monitored across the country by the appropriate agencies, among others were recommended.